Toll-like receptor expression in monocytes in patients with chronic kidney disease and haemodialysis: relation with inflammation - AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; KOÇ, MEHMET; ODABAŞI, ZEKAVER (OXFORD UNIV PRESS, 2011)
Background. Inflammation is one of the main contributors to atherosclerosis in haemodialysis (HD) patients. Activation of Toll-like receptors (TLRs) leads to inflammatory response. In this study, we aimed to evaluate the expression of TLRs on monocytes and relate their expression with inflammation in chronic kidney disease (CKD) and HD patients. Methods. Thirty-four age- and gender-matched controls and stage 3-4 CKD patients and thirty-two HD patients were included in each study group. The effect of HD on the expression of Toll-like receptor-2 (TLR-2) and Toll-like receptor-4 (TLR-4) on CD14(+) monocytes was determined at the beginning (baseline), during (120 min) and following (300 min and 24 h) HD and compared with control and stage 3-4 CKD groups. The HD procedure was performed by using low-flux polysulphone dialysers. In addition, serum IL-6 levels were evaluated in both groups at baseline and after a HD session. Results. The percentage of CD14(+) monocytes expressing TLR-2 were similar in all of the study groups, whereas the percentage of CD14(+) monocytes expressing TLR-4 were significantly lower in both stage 3-4 CKD and HD patients at baseline than in controls. The mean fluorescence intensities (MFI) of TLR-2 were significantly lower in controls than in stage 3-4 CKD and HD patients at baseline. The MFI of TLR-4 was similar in all of the groups. The percentage of CD14(+) monocytes expressing TLR-2 did not change during and after HD. The MFI of TLR-2 decreased at 120 min of HD compared with baseline (1837 +/- 672 vs 1650 +/- 578, P < 0.05), and recovered back to baseline values at 300 min and at 24 h post-HD. MFI of TLR-4 increased at 24 h compared with baseline (941 +/- 294 vs 1087 +/- 441, P < 0.05). Serum IL-6 levels correlated with MFI of TLR-2 and TLR-4 in stage 3-4 CKD patients and in HD patients at baseline and after HD in univariate analysis. Stepwise multiple regression analysis revealed that MFI of TLR-2 was an independent determinant of serum IL-6 concentrations in stage 3-4 CKD and in HD patients at baseline, at 300 min and at 24 h post-HD. Conclusions. Our study demonstrates that TLR-2 is associated with the inflammatory response of non-dialysed and dialysed CKD patients.
Keywords: chronic kidney disease; haemodialysis; inflammation; Toll-like receptor; PERIPHERAL-BLOOD LEUKOCYTES; TUMOR-NECROSIS-FACTOR; STAGE RENAL-DISEASE; INNATE IMMUNITY; TOLL-LIKE-RECEPTOR-4; INDUCTION; CELLS; INTERLEUKIN-6; ACTIVATION; CYTOKINES